Cardiovascular Outcomes Comparison of Dipeptidyl Peptidase-4 Inhibitors versus Sulfonylurea as Add-on Therapy for Type 2 Diabetes Mellitus: a Meta-Analysis - Jeon, Won Kyeong; Kang, Jeehoon; Kim, Hyo-Soo; Park, Kyung Woo (Journal of lipid and atherosclerosis, 2021)
Recent studies have raised concern about the cardiovascular safety of dipeptidyl peptidase-4 (DPP4) inhibitors. We performed a systematic review through meta-analysis to compare cardiovascular outcomes of sulfonylurea (SU) versus DPP4 inhibitors when used in combination with metformin. After searching for trials using combination therapy of metformin with DPP4 inhibitor or SU in PubMed, Cochrane Library, and Embase, one prospective observation study and 15 randomized controlled studies were selected. Regarding the primary analysis endpoint, there were no significant differences in the risk of all-cause mortality between SU and DPP4 inhibitors as an add-on therapy to metformin (random-effect relative risk [RR], 1.14; 95% confidence interval [CI], 0.98-1.33; =0.811; I =0%). Cardiovascular death was also similar between the two drug classes in the five studies which reported outcomes (random-effect RR, 1.03; 95% CI, 0.83-1.27; =0.517; I =0%). Furthermore, there were no significant differences in major adverse cardiac events (MACE), coronary heart disease, myocardial infarction, ischemic stroke and heart failure. However, there were less hypoglycemic events and weight gain in the DPP4 inhibitor group as compared with the SU group (random-effect RR, 3.79; 95% CI, 1.53-9.39; <0.001; I =98.2 and weighted mean difference, 1.68; 95% CI, 1.07-2.29; <0.001; I =94.7, respectively). As add-on therapy to metformin, there were no significant differences in all-cause mortality and cardiovascular mortality between DPP4 inhibitors and SUs.